Collaborative optimization of fuel composition and operating parameters of gasoline compression ignition (GCI) engine in a wide load range. (15th February 2022) - Zhang, Pengwei; Xu, Guangfu; Li, Yaopeng; Cai, Yikang; Duan, Huiquan; Jia, Ming
Highlights: Fuel compositions and operating parameters of GCI are collaboratively optimized in a wide range. The dominant effect of fuel properties on GCI combustion is significant with the increase of load. High-reactivity fuel is required at low and mid loads, and low-reactivity fuel is optimal at high load. Toluene can alleviate the heat release rate and reduce RI at high load. Abstract: Through the integration of three-dimensional computational fluid dynamics (CFD) simulation and genetic algorithm, the operating parameters and fuel composition of a gasoline compression ignition (GCI) engine were simultaneously explored in the full load range. The blends of n-heptane, iso -octane, and toluene were utilized as the substitute for real gasoline fuels, in which toluene can efficiently diminish the heat release rate so that excessively high ringing intensity (RI) can be avoided at high load by extending combustion duration. The synergistic effects of fuel properties and operating parameters on combustion and emissions were analyzed. In addition, the fuel composition requirements of GCI combustion were further discussed. The optimization results indicate that the collaborative optimization can achieve low nitrogen oxides (NOx ) emissions, near-zero soot emissions, and satisfactory fuel consumption under the GCI strategy. The combustion procedure was dominated by initial temperature and pressure at low load, and the effect of fuel characteristics is strengthened with higher load. The optimal combustion phasing of the GCI engine is postponed with the increase of load, which can enhance the temperature and fuel stratifications in the cylinder to prevent unacceptable RI. To minimize NOx emissions, a high proportion of n-heptane is preferred at low load and the contents of iso -octane and toluene approach to zero. Fuel research octane number (RON) has an inconspicuous impact on GCI at low load, and the fuel with higher RON can perform well at low load, except for the slightly higher NOx and soot emissions for high RON fuels. With the increase of load, the proportion of n-heptane decreases, which is compensated by the higher proportion of iso -octane. At high load, a certain amount of toluene is required, and high soot emissions are the main factor to limit the adoption of low RON fuels. Overall, GCI engine can utilize the fuel with RON between 70 and 80 in a wide load range.